Comparison of Efficacy and Safety of Injectable Levetiracetam and Phenytoin in the Management of Neonatal Seizures - Waqas Ahmad, Tooba Anam, Muhammad Zahid Farooq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the efficacy and safety between intravenous levetiracetam and phenytoin in the control of neonatal seizures. Methodology: The current pediatric study was a randomized controlled, open-label and parallel-group designed study. This study was carried out in the Department of Pediatric Medicine (Neonatal Emergency) at The Children Hospital and Institute of Child Health at Multan duration Study was January to October 2023. One hundred and thirty infants with persistent seizures were randomly divided into two cohorts where each numbered 65. Patients that received levetiracetam were assigned to group A and those that received phenytoin were assigned to group B. The outcome of the patients was monitored in terms of the adverse reaction and time elapsed to resolve the seizures. Efficacy and safety of levetiracetam versus phenytoin were used as primary outcomes to measure. Results: The properties of levetiracetam, namely its safety and efficacy profile proved to be superior to that of phenytoin. There were no reports of respiratory and cardiac depression in neonates treated with Levetiracetam, and on the other hand phenytoin had been associated with depression on respiration (6.15%), and cardiac (1.53 %). Fewer cases of hypotension were witnessed in the Levetiracetam group. Moreover, Levetiracetam proved to be linked with faster cessation of seizures within 30 minutes (95.38 % vs. 90.77 %) and higher efficacy (95.38 % vs. 90.77 %, p=0.0128). The safety drug was also better in the Levetiracetam group (96.92 % vs. 87.69 %, p=0.022). Conclusion: The results of this study justify the claim that lacosamide (LEV) is safer and more effective than phenytoin in treating neonatal seizures among the preterm infants. Keywords: Levetiracetam, Phenytoin, Neonatal Seizures, Safety, Children, Health.